Canis mosbachensis (Canidae, Mammalia) dal Pleistocene Medio di Contrada Monticelli (Putignano, Puglia, Italia meridionale). - Mecozzi, Beniamino; IURINO, DAWID ADAM; BERTÉ, DAVIDE FEDERICO; SARDELLA, Raffaele (2017)
Herein we describe for the first time a canid partial cranium from the Contrada Monticelli site. Morphological and biometrical studies allow the fossil remains to be referred to the Middle Pleistocene wolf Canis mosbachensis. Associated taxa include Paleoloxodon antiquus, Stephanorhinus hundsheimensis, cervids, equids and bovids, whose biochronological occurrence allows the site to be referred to the Galerian Mammal Age. Diagnostic characters normally used to distinguish Canis mosbachensis from Canis lupus are herein discussed. These carnivorans show a wide range in body-size and morphological variability, related to an extensive geographical distribution. The analyzed fossil can be considered as the smallest European specimen referable to the Mosbach wolf and represents the southernmost occurrence of this taxon in Italy.